Greytown: the oldest inland colonial town - Kernohan, David (Architectural History Aotearoa, 2018)
Greytown is the oldest town in the Wairarapa established under the Small Farms Association, and the oldest inland settlement of the British colonial era. In March 1854, at a meeting held in the Crown and Anchor Hotel in Wellington, 49 settlers selected town acres in Greytown. By the 1870s Greytown had its own newspaper, a school, a hospital and a flourishing retail and commercial base. In 1871 the Greytown Trust Act was passed and the town became a centre for farming, flax, and timber milling though it suffered from the regular flooding of the Waiohine river. Greytown became a borough in 1878 but stopped growing when the railway by-passed it. This paper explores the extant buildings from that period and issues around maintaining the Greytown Historic Heritage Precinct.